2014
DOI: 10.4103/0972-6748.151673
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity in elderly patients attending OPD of tertiary care centre in western region of Nepal

Abstract: Context:Aging of population is currently a global phenomenon. At least one in 5 people over the age of 65 years will suffer from a mental disorder by 2030. Study of psychiatric morbidities in this age group is essential to prepare for upcoming challenges.Aims:To find out the prevalence of different psychiatric morbidities in elderly population and to find out if there are any age and gender specific differences.Settings and Design:Retrospective review; Psychiatric outpatient department of Manipal Teaching Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Pooled studies of GDS-15 indicated a sensitivity of 80.5%and specificity of 75%with optimal cut off 5/6 [8]. Depressive disorder was the most common psychiatric morbidity among the elderly patients [9]. Just like other non-communicable disease depression too has various risk factors [10].…”
Section: Original Research Articlementioning
confidence: 99%
“…Pooled studies of GDS-15 indicated a sensitivity of 80.5%and specificity of 75%with optimal cut off 5/6 [8]. Depressive disorder was the most common psychiatric morbidity among the elderly patients [9]. Just like other non-communicable disease depression too has various risk factors [10].…”
Section: Original Research Articlementioning
confidence: 99%
“…It is only of late that we have few more published studies and reviews on geropsychiatric patients in Nepal. 20,27 Present study is expected to add some more light on this sub-specialty in Psychiatry and hope to induce more interest among young researchers to carry our further research among geriatric psychiatric patients in Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…Nepalese OPD based studies have reported AUD in range of 10.5% to 14%. 10,11,17,22 In our study prevalence of BPAD (including first episode mania) was 5.06%. Reported prevalence of mania amongst geriatric people is found to be low (1-2%) in both in-patient as well as community prevalence studies from western countries.…”
Section: Characteristicsmentioning
confidence: 44%